Atomic layer deposition-triggered hierarchical core/shell stable bifunctional electrocatalysts for overall water splitting. Issue 37 (2nd September 2021) - Kavinkumar, T.; Seenivasan, Selvaraj; Jung, Hyeonjung; Han, Jeong Woo; Kim, Do-Heyoung
Abstract : A synergistic strategy of interface engineering and surface modification is efficient to construct a promising bifunctional electrocatalyst for enhanced electrocatalytic water splitting. Abstract : The precise design of nanomaterials is a promising approach, but remains a challenge toward the development of highly efficient catalysts in water splitting applications. Herein, a facile three-step process to rationally design advanced NiCo2 O4 /MoO2 @atomic layer deposition (ALD)-NiO heteronanostructure arrays on a nickel foam substrate is reported. By effective interface construction, the optimal electronic structure and coordination environment are created at the interface in the heteronanostructure, which can provide rich reaction sites and short ion diffusion paths. Notably, density functional theory calculations reveal that the MoO2 @ALD-NiO nanointerface exhibits highly appropriate energetics for alkaline oxygen/hydrogen evolution reactions (OER/HER), thereby accelerating the enhancement in electrochemical activities. Benefiting from the heteronanostructure containing abundant nanointerfaces, NiCo2 O4 /MoO2 @ALD-NiO displays remarkable HER (57.1 mV at 10 mA cm −2 ) and OER (372.3 mV at 100 mA cm −2 ) activities and excellent long-term stability in a 1 M KOH solution. This study provides new insight into the catalytic design of cost-effective electrocatalysts for future renewable energy systems.